2017
DOI: 10.1587/transele.e100.c.283
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Transition Edge Sensor for Gamma-Ray Spectroscopy

Abstract: SUMMARY Superconducting Transition edge sensor (TES) coupled with a heavy metal absorber is a promising microcalorimeter for Gammaray (γ-ray) spectroscopy with ultra-high energy resolution and high detection efficiency. It is very useful for the non-destructed inspection of the nuclide materials. High resolving power of γ-ray peaks can precisely identify multiple nuclides such as Plutonium (Pu) and Actinides with high efficiency and safety. For this purpose, we have developed the TES coupled with a tin absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Whereas different absorber materials have been tested extensively for x-ray microcalorimeters, fewer studies have been completed for γ-ray microcalorimeters. 50,51 Given that the performance of γ-ray microcalorimeters is limited by phonon noise that scales with the heat capacitance of the absorbers, the selection of an absorber material with low specific heat capacity is particularly important for these γ-ray detectors.…”
Section: Optimization Of the 511-cam Focal Plane Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas different absorber materials have been tested extensively for x-ray microcalorimeters, fewer studies have been completed for γ-ray microcalorimeters. 50,51 Given that the performance of γ-ray microcalorimeters is limited by phonon noise that scales with the heat capacitance of the absorbers, the selection of an absorber material with low specific heat capacity is particularly important for these γ-ray detectors.…”
Section: Optimization Of the 511-cam Focal Plane Instrumentationmentioning
confidence: 99%
“…This factor, along with vibrational noise from the dilution refrigerator, potentially contributes to the slightly worse-than-expected energy resolution. 51 The motivation for using Bi 0.57 Sn 0.43 is to make an absorber material that combines the high stopping power of Bi with the low heat capacitance of a superconductor that transitions at a higher, easier temperature. While the transition temperature of Sn at ambient pressures is 3.72 K, that of Bi is estimated to be <1.3 mK; 58,59 Prakash et al reported 0.53 mK.…”
Section: Optimization Of the 511-cam Focal Plane Instrumentationmentioning
confidence: 99%
“…Whereas different absorber materials have been tested extensively for X-ray micro-calorimeters, fewer studies have been completed for γ-ray microcalorimeters. 52,53 Given that γ-ray microcalorimeters require macroscopic absorbers to stop the γ-rays, a low heat capacitance is relatively important for these detectors. We consider four materials as options for the 511-CAM absorbers: Sn (the material currently used on the SLEDGEHAMMER detectors), Ta, Bi, or a Bi 0.57 -Sn 0.43 alloy (see Table 1).…”
Section: Optimization Of the 511-cam Focal Plane Instrumentationmentioning
confidence: 99%
“…Indeed, Ohno et al already demonstrated that a microcalorimeter with small 0.5×0.5×0.3 mm 3 Ta absorbers achieves a 445 eV FWHM energy resolution at 662 keV, and thus solidly outperforms HPGe detectors. 53 We utilized a 511 keV near-field source whose profile is given by the concentrated radial beam on the focal plane. An effective observation time of 1 Ms has been assumed for a balloon flight, and the flux was modified for the effects of atmospheric absorption.…”
Section: Simulations Of the Focal Plane Detectormentioning
confidence: 99%
“…While varnish or silver paste are used to mount a chip with low dissipation power such as superconducting sensors and so on [24,25], the use of them resulted in a significant temperature increase in the voltage standard chip due to large dissipation power. Thus, a silicon chip is solderbonded to a copper substrate to achieve good thermal contact between the chip and a cryocooler.…”
Section: Packaging For Cryocoolermentioning
confidence: 99%